2008
DOI: 10.1002/macp.200700605
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of PEG Crystallization on the Morphology of PEG/Peptide Block Copolymers Containing Amyloid β‐Peptide Fragments

Abstract: Ordered nanostructures are observed in the melt and solid state for a series of three peptide/PEG conjugates containing fragments of amyloid β‐peptides. These are conjugated to PEG with $\overline M _{\rm n}$ = 3 300 g · mol−1 and a melting temperature Tm = 45–50 °C. The morphology at room temperature is examined by AFM and POM. This shows spherulite formation for the weakly fibrillizing KLVFF‐PEG sample but fibril formation for FFKLVFF‐PEG. The fibrillization tendency of the latter is enhanced by multiple phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 29 publications
(32 reference statements)
2
40
0
Order By: Relevance
“…[38][39][40][41] Finally, b-sheet structures found in silks and amyloid proteins also have repetitive motifs. [5,42] Natural occurring silk consists of b-sheet crystalline segments that alternate with amorphous segments. [2] The crystalline segment of B. mori silk is represented by GAGAGS repeat; whereas, N. clavipes spidroin crystalline segment is made of polyalanine or poly(alanylglycine) residues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[38][39][40][41] Finally, b-sheet structures found in silks and amyloid proteins also have repetitive motifs. [5,42] Natural occurring silk consists of b-sheet crystalline segments that alternate with amorphous segments. [2] The crystalline segment of B. mori silk is represented by GAGAGS repeat; whereas, N. clavipes spidroin crystalline segment is made of polyalanine or poly(alanylglycine) residues.…”
Section: Resultsmentioning
confidence: 99%
“…The unit cell dimensions for the crystalline component of the dragline silk of N. clavipes have been found to be a ¼ 0.93 nm, b ¼ 1.04 nm, and c ¼ 0.70 nm, corresponding to a repeat distance of b-sheets, interchain repeat within b-sheets, and intrachain repeat, respectively. [67] Since in the b-strand conformation one amino acid residue contributes 0.35 nm along the molecular chain direction, [42] we expect that the length of one polyalanine block in BA6 peptide will be 4.2 nm. Then the total length of the crystalline segment including all units will be 25.2 nm ( Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that there is a competition between peptide fibrillisation and PEG crystallization in PEG-peptides. In particular, we investigated the series in increasing order of peptide fibrillisation tendency, KLVFF-PEG, AAKLVFF-PEG and FFKLVFF-PEG (all with PEG M n = 3000 g mol − 1 ) [48,49]. In KLVFF-PEG, PEG crystallization strongly disrupted the peptide β-sheet formation, however for FFKLVFF-PEG, PEG crystallization did not occur at the expense of peptide secondary structure formation.…”
Section: Peg Crystallization In Dried Filmsmentioning
confidence: 99%
“…For example, the peptide/protein segment can allow enhanced control over nanoscale structure formation of the synthetic component. The synthetic segment can also reduce toxicity and immunogenicity, and prevent enzymatic degradation or loss of function due to unfolding of the peptide/protein component 48, 49.…”
Section: Synthetic Polymer Peptide Block Copolymersmentioning
confidence: 99%
“…There are diverse routes to prepare hybrid block copolymers 46-48, 50, 51. Controlled radical polymerization, ring opening polymerization, polymerization of macromonomers, and convergent synthesis of peptide-polymer hybrids are some examples.…”
Section: Synthetic Polymer Peptide Block Copolymersmentioning
confidence: 99%